Anemia and Blood Transfusions in Critically Ill Patients. (22nd October 2012) - Athar, M. Kamran; Puri, Nitin; Gerber, David R.
Abstract : Anemia is common in critically ill patients. As a consequence packed red blood cell (PRBC) transfusions are frequent in the critically ill. Over the past two decades a growing body of literature has emerged, linking PRBC transfusion to infections, immunosuppression, organ dysfunction, and a higher mortality rate. However, despite growing evidence that risk of PRBC transfusion outweighs its benefit, significant numbers of critically ill patients still receive PRBC transfusion during their intensive care unit (ICU) stay. In this paper, we summarize the current literature concerning the impact of anemia on outcomes in critically ill patients and the potential complications of PRBC transfusions.